PENGEMBANGAN MEDIA “SERUNYA BELAJAR ORGAN GERAK HEWAN DAN MANUSIA” BERBASIS POWERPOINT DI KELAS V SEKOLAH DASAR - Rezan Rezan; Dian Nuzulia Armiena; Sylvia Lara Syaflin (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2023)
This researcher aims to produce (1) validation results for powerpoint media products which in terms of media, material and language obtained an average of 88.9% in the "Very Valid" category (2) Results of one-to-one trials conducted with three students obtained good responses. (3) The results of the small group trial conducted on 20 students and obtained a score of 96.3% in the "Very Practical" category. This PowerPoint media has been developed based on its benefits and uses. Based on the results of the potential effect trial, powerpoint can be used by educators because the research results have shown valid, practical, and effective potential criteria. This product can be used in material for movement and human organs in class V science learning at SD Negeri 136 Palembang.